2022
DOI: 10.1186/s12891-022-05305-w
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable implants vs. Kirschner-wires in the treatment of severely displaced distal paediatric radius and forearm fractures – a retrospective multicentre study

Abstract: Background Distal radius fractures are very common in paediatric patients. Severely displaced fractures may require surgical intervention. The gold standard surgical method is percutaneous K-wire osteosynthesis followed by immobilisation. Metal implants can be removed with a second intervention; however, these extra procedures can cause further complications. Several studies confirm the benefits of bioabsorbable implants for paediatric patients. The aim of this retrospective study was to compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Within a retrospective multicentre study in Hungary during the period between January 2019 and January 2020 of 26 children aged between five and 12 years with severely displaced distal metaphyseal radial fractures, six patients are treated with biodegradable poly(L-lactide)-co-glycolide acid implants (Bioretec®, ActivaPin®), while 13 children are treated with one or two stainless steel Kirschner-wires (Sanatmetal®) buried under the skin and seven ones are managwed with Kirschner-wires left outside the skin (Varga et al, 2022). In the first group, the complication rate is statistically significantly lower and no second surgical intervention is required.…”
Section: Discussionmentioning
confidence: 99%
“…Within a retrospective multicentre study in Hungary during the period between January 2019 and January 2020 of 26 children aged between five and 12 years with severely displaced distal metaphyseal radial fractures, six patients are treated with biodegradable poly(L-lactide)-co-glycolide acid implants (Bioretec®, ActivaPin®), while 13 children are treated with one or two stainless steel Kirschner-wires (Sanatmetal®) buried under the skin and seven ones are managwed with Kirschner-wires left outside the skin (Varga et al, 2022). In the first group, the complication rate is statistically significantly lower and no second surgical intervention is required.…”
Section: Discussionmentioning
confidence: 99%
“…Varga et al [13] published a comparative study of the treatment of 94 distal fractures of the radius, associated or not with ulna fractures. One group treated with one or two stainless steel Kirschner wires which were buried under the skin (n = 40), a second group with K-wire left outside (n = 24) and the third group with an original technique of distal radial elastic nailing with bioresorbable PLGA pins (n = 30).…”
Section: оригинальные статьиmentioning
confidence: 99%
“…Poor molding and overfilling of the cast is a known cause of a loose-fitting cast which may lead to repositioning [5]. Most surgeons recommend osteosynthesis if the fracture is unstable after reduction [6]. Proctor et al [7] suggested fixation in all cases where perfect reduction could not be achieved, while Prevot et al [8] recommended wire fixation for unstable or irreducible fractures.…”
Section: Introductionmentioning
confidence: 99%